2013
DOI: 10.1007/s12603-012-0408-2
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition and falls risk in community-dwelling older adults

Abstract: There was a low prevalence of malnutrition risk in this sample of community-dwelling older adults and no association between nutritional risk and falls. Screening as part of a falls prevention program should focus on the risk of developing malnutrition as this is associated with falls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…In the present study, no association was found between being malnourished and a low MMSE score which is in line with previous studies [ 6 , 14 ] in a population of geriatric patients.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, no association was found between being malnourished and a low MMSE score which is in line with previous studies [ 6 , 14 ] in a population of geriatric patients.…”
Section: Discussionsupporting
confidence: 93%
“…A plausible mechanism for these findings could be that low phase angle might reflect a condition inclusive of multiple risk factors for falls, such as sarcopenia, physical inactivity and malnutrition, all of which have been reported to increase the risk of falls in older adults . Age, sex, fluid distribution, body mass index and inflammation are known as basic determinants of phase angles .…”
Section: Discussionmentioning
confidence: 98%
“…Fall-related injury emerges as an important cause of morbidity and mortality in the elderly (29). Damages caused by falling lead to an increase in nursing home admission and dependence (30). The results of studies on nutritional status and fall risk in the literature are contradictory.…”
Section: Discussionmentioning
confidence: 99%